Nitrogen‑potassium ratios in fertirrigation for protected cultivation of tomato in Red Ferralitic soil - Díaz, María Isabel Hernández; Laffita, Marisa Chailloux; Placeres, Victor Moreno; Veloz, Anselma Ojeda; Pulido, Julia Mirta Salgado; Guerrero, Odalis Bruzón (Pesquisa Agropecuaria Brasileira, 2010)
The objective of the present work was to evaluate the effect of nutrient solutions in fertirrigation, with different nitrogen–potassium ratios, on yield and quality of tomato fruits (hybrid Hazera 3019) in Red Ferralitic soil (Oxisol). The trial was performed at Instituto de Investigaciones Hortícolas Liliana Dimitrova (La Habana, Cuba). Four nutrient solutions were studied, which were different in their NO3-+NH4+/K+ ratios in terms of meq L-1 (N/K), keeping a K+/Ca2++Mg2+ ratio of 0,75 in every variant. The resulting treatments (T1, 1:0.45; T2, 1:0.60 or production test control, T3, 1:0.75 and T4, 1:0.90) were distributed in a completely randomized design with four replicates. The N/K ratio variation in the nutrient solution influenced the yield, external quality and postharvest life of tomato fruits, without affecting the bromatologic quality. The best combination of yield structure and fruit quality was obtained with the 1:0.75 N/K ratio, which had superior yield in extra, first and extra plus first commercial qualities, as well as fruits with higher firmness and larger endocarp thickness, lesser abnormal fruit percentage and lower postharvest losses.